Determining optimal two-crop succession using mixed integer linear programming (MIP) for self-financed farmers in Kapatagan, Digos, davao del Sur - Delica, Shirley V. (2006)
Mixed Integer Programming (MIP) model was formulated to determine the optimal two-crop succession for self-financed farmers in Kapatagan, Digos, Davao del Sur. The main objective of the MIP model was to maximize the net profit of the self-financed farmers taking into consideration environmental constraint and subject to the limited agricultural resources such as land, labor, and capital. Activities of the model include decisions with regards to what crops should to be planted in a particular season and its land allocation. Optimal two-crop succession was determined given a land area available. MILP software was used to solve the model. The optimal two-crop succession includes planting carrot and corn for season 1, cabbage and Chinese cabbage for season 2 provided that there is no infested crop, carrot and potato for season 3, yielding a high income for the farmers. On the land, allocation, the most profitable crop planted in a particular season was allotted more land area compared to the less profitable. With its results, sensitivity analysis was applied to determine the range of optimality of the parameters. Through the implementation of the MIP model, the method has rendered results that can be useful and beneficial for the farmer in Kapataga